Effect of the NFIB rs28379954 T>C polymorphism on CYP2D6‐catalyzed metabolism of solanidine - Robert Løvsletten Smith; Birgit M. Wollmann; Elisabet Størset; Hasan Çağın Lenk; Kevin S. O'Connell; Marianne Kringen Kristiansen; Magnus Ingelman‐Sundberg; Espen Molden (Wiley, 2024)
Abstract Cytochrome P450 2D6 (CYP2D6) is important for metabolism of 20%-25% of all clinically used drugs. Many known genetic variants contribute to the large interindividual variability in CYP2D6 metabolism, but much is still unexplained. We recently described that nuclear factor 1B (NFIB) regulates hepatic CYP2D6 expression with the minor allele of NFIB rs28379954 T>C significantly increasing CYP2D6‐mediated risperidone metabolism. In this study, we investigated the effect of NFIB T>C on metabolism of solanidine, a dietary CYP2D6 substrate. Analyses of solanidine and metabolites (M414, M416, and M444) were performed by ultra‐high performance liquid chromatography‐high‐resolution mass spectrometry in a cohort of 463 CYP2D6‐genotyped patients of which with 58 (12.5%) carried NFIB TC (n = 56) or CC (n = 2). Increased metabolism of solanidine was found in CYP2D6 normal metabolizers (NMs; n = 258, 55.7%) carrying the NFIB C variant (n = 27, 5.8%) with 2.83‐ and 3.38‐fold higher M416‐to‐solanidine (p = 0.039) and M444‐to‐solanidine (p = 0.046) ratios, respectively, whereas this effect was not significant among intermediate metabolizers (n = 166, 35.9%) (p ≥ 0.09). Importantly, no effect of the NFIB polymorphism on solanidine metabolism was seen in TC or CC carriers lacking CYP2D6 activity (poor metabolizers, n = 30, 6.5%, p ≥ 0.74). Furthermore, the NFIB polymorphism significantly explained variability in solanidine metabolism (M414 p = 0.013, M416 p = 0.020, and M416 and M444 p = 0.009) in multiple linear regression models for each metabolic ratio in the entire population, correcting for covariates (including CYP2D6 genotypes). Thus, the study confirms the effect of NFIB in regulating CYP2D6 activity, suggesting an about 200% increase in CYP2D6‐mediated clearance in NMs being NFIB CT or CC carriers, comprising around 6% of Europeans.